answersLogoWhite

0


Best Answer

-2

User Avatar

Doris Carter

Lvl 10
โˆ™ 2021-02-27 00:37:27
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
824 Reviews
More answers
User Avatar

Wiki User

โˆ™ 2010-06-07 15:11:52

Solving using the substitution method gives:

x = -1 and y = -3

This answer is:
User Avatar

User Avatar

Anonymous

Lvl 1
โˆ™ 2020-06-29 19:57:39

Substituting the equation x equals 2 y plus 3 into the equation y equals short dash 3 x minus 4 will produce the equation _________.

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Solve using substitution x minus y equals 2 and x plus y equals -4?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What 4x y14 and 2x y8 solve using substitution?

You cant solve it unless it is an equation. To be an equation it must have an equals sign.


How do you solve 0 equals x squared minus ten x plus 16?

Solve using the quadratic formula


What is the answer for the ordered pair form x plus 7y equals 39 3x minus 2y equals 2 using substitution?

If you mean: x+7y = 39 and 3x-2y = 2 Then by substitution: x = 4 and y = 5


How would use solve the system of equation x plus 3y equals 23 by using substitution?

You'd need another equation to sub in


Solve using substitution x plus y equals 3 and y equals 9?

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".


How do you solve x squared minus ten x plus six equals zero?

It can be solved by using the quadratic equation formula.


How do you solve a problem using substitution?

y=2x+9 and y=x+6


How do you solve x plus y equals 8 and 2x minus y equals 5 using the addition method?

If: x+y = 8 and 2x-y = 5 Then by adding the equations together: 3x = 13 or x = 13/3 By substitution into the original equations: x = 13/3 and y = 11/3


Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24?

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4


Can quadratic systems be solved using elimination and substitution?

You can solve lineaar quadratic systems by either the elimination or the substitution methods. You can also solve them using the comparison method. Which method works best depends on which method the person solving them is comfortable with.


How do you solve a problem using the substitution method?

You solve this by theoretically diverting the hypotenuse of the x divided by the overall beneficial procedure of y


What is indicated by the occurrence of a false statement such as 0 equals 1 when you solve a system of two linear equations in two variables using substitution?

In that instance, it means that the lines never touch.

People also asked